Viabilidade técnica, econômica e ambiental de um sistema ultrassônico para tratamento de água de caldeira. - Pedrosa Junior, Leonildo Pereira (2023)
The boiler is a piece of equipment of great importance for industrial processes, which, in addition to being included in production processes, are important in energy generation. The ability to generate steam for such processes requires water with a high degree of purity, a commodity that is becoming less and less today. The water that feeds the boiler needs to undergo treatments and controls in order to avoid its inefficiency, excessive costs and a risk to the safety of the plant that uses it. The water that feeds the boiler needs to undergo treatments and controls in order to avoid its inefficiency, excessive costs and a risk to the safety of the plant that uses it. The ultrasonic boiler feed water treatment system (STUAC), addressed in this study, promotes the separation of salts in the water by the combined humidification-dehumidification effect of a stream of atomized water mixed with hot air. The study aimed to demonstrate the technical, economic and environmental viability of the STUAC, comparing it with a Reverse Osmosis system in boiler water desalination. The EVTEA was implemented with the aid of a Microsoft® Excel spreadsheet. The results showed advantages such as low operation and maintenance costs, similar efficiency (99%), very low residual water content (<1.0%) and the non-use of chemical products in favor of STUAC.